Deaths While under Probation Supervision: What Role for Human Rights Legislation?. Issue 3 (6th September 2019) - Phillips, Jake; Gelsthorpe, Loraine; Padfield, Nicola
Abstract: Article 3 of the Universal Declaration of Human Rights (UDHR) states that 'everyone has the right to life'. This right is contained in all human rights treaties that developed from the UDHR, including the European Convention on Human Rights (ECHR). Yet, as we argue, the UK government is failing to protect this right when it comes to certain groups of people under probation supervision. To date, human rights legislation has failed adequately to protect these vulnerable individuals and to hold the state to account. This article explores the greater potential for using human rights legislation to ensure better accountability in this area.